Factors Predicting Willingness to Share COVID-19 Misinformation - Lobato, Emilio J. C.; Powell, Maia; Padilla, Lace M. K.; Holbrook, Colin (Frontiers in Psychology, 2020)
We conducted a preregistered exploratory survey to assess whether patterns of individual differences in political orientation, social dominance orientation, traditionalism, conspiracy ideation, or attitudes about science predict willingness to share different kinds of misinformation regarding the COVID-19 pandemic online. Analyses revealed two orthogonal models of individual differences predicting the willingness to share misinformation over social media platforms. Both models suggest a sizable role of different aspects of political belief, particularly social dominance orientation, in predicting tendencies to share different kinds of misinformation, predominantly conspiracy theories. Although exploratory, results from this study can contribute to the formulation of a socio-cognitive profile of individuals who act as vectors for the spread of scientific misinformation online, and can be useful for computationally modeling misinformation diffusion.